Investigating pragma-rhetorical strategies utilized by American commencement speakers to motivate graduates for managing future opportunities and challenges - Mubarak, Ahmed Sahib; Rhaif, Kadhim Ketab (Linguistics and Culture Review, 2021)
Motivating emotions is a critical factor in empowering students to manage the troubles they might face. Educational organizations pay great efforts to employ all the available means that can motivate their students for better learning from early stages until universities or institutes levels. The administrations of some universities and institutes, especially in the United States of America, do not stop there and pay more attention on motivating their students at the graduation parties on how to manage future businesses and challenges. This study explores how commencement speakers utilize success stories pragma-rhetorically to motivate the graduates to behave wisely to take future decisions. It investigates the pragmatic-rhetorical strategies in the motivational storytelling that is delivered within commencement speeches at American universities and institutes. It aims to recognize and analyze these strategies that commencement speakers employ as strategic strategies in presenting their stories to achieve their motivational purposes. More specifically, it explores how speech acts, rhetorical tropes, conversational implicatures, and rhetorical appeals are used and distributed in the storytelling discourse. To this end, the researchers selected ten commencement speeches delivered by American commencement speaker.